Mild Hydrogenation of Amides to Amines over a Platinum‐Vanadium Bimetallic Catalyst. (6th July 2017) - Mitsudome, Takato; Miyagawa, Kazuya; Maeno, Zen; Mizugaki, Tomoo; Jitsukawa, Koichiro; Yamasaki, Jun; Kitagawa, Yasutaka; Kaneda, Kiyotomi
Abstract: Hydrogenation of amides to amines is an important reaction, but the need for high temperatures and H2 pressures is a problem. Catalysts that are effective under mild reaction conditions, that is, lower than 30 bar H2 and 70 °C, have not yet been reported. Here, the mild hydrogenation of amides was achieved for the first time by using a Pt‐V bimetallic catalyst. Amide hydrogenation, at either 1 bar H2 at 70 °C or 5 bar H2 at room temperature was achieved using the bimetallic catalyst. The mild reaction conditions enable highly selective hydrogenation of various amides to the corresponding amines, while inhibiting arene hydrogenation. Catalyst characterization showed that the origin of the catalytic activity for the bimetallic catalyst is the oxophilic V‐decorated Pt nanoparticles, which are 2 nm in diameter.